Electromagnetic control of heat transport within a rectangular channel filled with flowing liquid metal. (6th November 2017) - Modestov, M.; Kolemen, E.; Fisher, A.E.; Hvasta, M.G.
Abstract: The behavior of free-surface, liquid-metal flows exposed to both magnetic fields and an injected electric current is investigated via experiment and numerical simulations. The purpose of this paper is to provide an experimental and theoretical proof-of-concept for enhanced thermal mixing within fast-flowing, free-surface, liquid-metal plasma facing components that could be used in next-generation fusion reactors. The enhanced hydrodynamic and thermal mixing induced by non-uniform current density near the electrodes appears to improve heat transfer through the thickness of the flowing metal. Also, the outflow heat flux profile is strongly affected by the impact of the J   ×   B forces on flow velocity. The experimental results are compared to COMSOL simulations in order to lay the groundwork for future liquid-metal research.